MECHANISM FOR THE ADJUSTMENT OF ADVANCED HEATING - Устинова, Ірина Петрівна; Ярошук, Марина Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: in the article the features of the state regulation mechanism are considered. The understanding of such a subject is formulated. The characteristics of their status indicators are highlighted. Three structural levels are proposed in their system. Methods of research: the legal mechanism of aviation transportation has been analyzed and defined. Results: the mechanism of legal regulation of aviation transportation is investigated. A conclusion is drawn about the adequacy of the existing regulation and proposals for their improvement. Discussion: national legislation on the effectiveness of the mechanism created.